The Effects of Cognitive-Behavioral Counseling on Self-esteem and the Tendency of Mobile Phone Addiction: Array - Belardo Farjantoky; Sunawan Sunawan; Mulawarman Mulawarman (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2020)
The mobile phone users in students are increased dramatically. Unfortunately, excessive use of mobile phone could cause addiction. The addiction to mobile phone affecting the personal and social life of students. Therefore, authors decided to identify the effect of cognitive-behavioral counseling interventions on self-esteem and the tendency of mobile phone addiction in students of Vocational School 1 Muhammadiyah Semarang. Participants in the pretest were 120 students. This study used a quasi-experiment method, pretest-posttest control group design involving 12 students, randomly divided to experiment (6 students) and control group (6 students). The samples were selected using purposive sampling with low self-esteem criteria and a high tendency for mobile phone addiction. The MANCOVA test results proved that cognitive-behavioral counseling had an effect on self-esteem (F1.8=265.28; ηp2=0.963; p<0.001), and the tendency of mobile phone addiction (F1.8=1115.90; ηp2=0.973; p<0.001). The findings of this study proved that there were effects of cognitive-behavioral counseling interventions on self-esteem and the tendency of mobile phone addiction.